PENERAPAN WEBSITE BLOGGER SEBAGAI INOVASI PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN KOMPETENSI MENULIS SISWA SMP NEGERI 14 PEKALONGAN - kamilah, Arina Kharisatul; Eliza, Naila Nur; Alawiyah, Vina Vitri; Syahda, Talitha Ulima; Pujiono, Imam Prayogo (Muntaha Noor Institute, 2026)
The rapid development of digital technology has encouraged Indonesian language learning, particularly writing skills, to integrate technology-based instructional media. However, the use of digital media in teaching writing at the junior high school level remains limited. This study aims to examine the implementation of Blogger as a digital learning innovation to improve students’ writing competence at SMP Negeri 14 Pekalongan. This research employed a descriptive qualitative approach, with data collected through classroom observations, documentation of students’ writing published on Blogger, and reflective notes from teachers and researchers. The research subjects were eighth-grade students selected through purposive sampling. The findings indicate that the use of Blogger enhances students’ interest, engagement, and writing competence through online writing, revision, and publication activities. Students became more active, reflective, and confident in expressing ideas in written form. Nevertheless, several technical and non-technical challenges were identified, including limited internet access and varying levels of digital literacy. Overall, Blogger is proven to be an effective digital learning medium for writing instruction, supporting digital literacy development and 21st-century skills among junior high school students.